El Tribunal Constitucional, un balance de cuarenta años - Carrillo, Marc (Revista de Derecho Político, 2018)
Resumen: La previsión de la jurisdicción constitucional en la Constitución de 1978 ha sido un instrumento que ha reforzado su condición de norma jurídica. El indudable prestigio institucional del Tribunal Constitucional adquirido en los primeros años se ha visto reducido posteriormente por la influencia política en su composición y funcionamiento. La interpretación constitucional forma parte de la Teoría de la Constitución y los criterios hermenéuticos del empleados por el Tribunal han tenido una notable influencia en la jurisdicción ordinaria. Por otra parte, el sentido objetivo y las nuevas reglas sobre admisión del recurso individual (amparo), han permitido que el Tribunal pueda ejercer con mayor eficacia el juicio sobre la ley del Parlamento. Por otra parte, su función de garantía de los derechos fundamentales no puede ser concebida al margen del sistema europeo de jurisdicción multinivel. Abstract: The provision of constitutional jurisdiction in the 1978 Constitution has been an instrument that has reinforced its status as a legal norm. The undoubted institutional prestige of the Constitutional Court acquired in the first years has been subsequently reduced by political influence on its composition and functioning. The constitutional interpretation forms part of the Theory of the Constitution and the hermeneutical criteria of the employees by the Court have had a notable influence in the ordinary jurisdiction. On the other hand, the objective meaning and the new rules on admission of the appeal for Constitutional rigth’s legal protection (amparo), has allowed the Court to exercise more effectively the judgment on the law of Parliament. On the other hand, its function of guaranteeing fundamental rights can not be conceived outside the European system of multilevel jurisdiction. Summary: 1. The constitutional justice and the Constitutional Court. 2. The constitutional interpretation. 3. The control of constitutionality of the law. 4.-The objective meaning of the appeal for Constitutional rigth’s legal protection (amparo). 5. The conflicts of competences: the constitutional jurisdiction and the ordinary jurisdiction. 6. The sentence of the Constitutional Court and the Dissenting vote’s function.